“Another brick in the wall”? Teachers’ conceptions about assessment: the views of teacher trainees - Pastore, Serafina; Pentassuglia, Monica (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2015)
Nowadays, educational research points out how teaching-learning quality is interwoven with teachers’ conceptions of teaching, learning, curriculum, and assessment. Starting from a preliminary review of main international inquiries on teachers’ assessment conceptions, this paper tries to reflect on teachers’ trainees conceptions about assessment.